Avaliação clinica do uso do dispositivo intra-uterino T-Cu 200B em adolescentes - Ribeiro, Gizelda Nogueira de Oliveira, 1943-2000 (1997)
Orientadores: Abraham Juan Antonio Diaz Moraguez, Luis Bahamondes